BOEKHANDEL TAN KHOEN SWIE KEDIRI: THE AGENT OF JAVANESE CULTURE - Wisnu, Wisnu (History Department, Semarang State University and Historian Society of Indonesia, 2019)
This paper reveals the way Boekhandel Tan Khoen Swie Kediri, as an agent of Javanese culture, run his publishing house during amidst both the colonial government and Indonesian government, spreading Javanese culture to the society in Java and throughout Indonesia. The history of this publishing house is interesting in which it is interrelated with three different policies from three different types of government ideology. This research which means searching, criticizing, interpreting, and arranging the sources in the form of historical writing. This research also applied GiddenÃ¢â‚¬â„¢s theory of structuration to clarify the position of Tan Khoen as a publishing agent. The discussion on the structure of the literary society, which consisted of the representatives from the government, authors, publishers, and readers becomes an integral part of the study. This study concludes both the government and private publishers had an intention to educate people although Tan Khoen Swie did not tied its theme on the existing system. However structurally, the existence Boekhandel Tan Khoen Swie were bounded by the authors, other publishers, and readers. The seasons for publishing Javanese culture books because the books contained noble culture, which needs to be disseminated, the legitimation of Javanese writers, and promising market prospect. The success of Tan Khoen Swie business lies in its ability to build networking among authors, publishers, and readers or bookstores. The books published in his business spread across Indonesia. He served both as a cultural broker and as an agent of Javanese culture.Keywords: Tan Khoen Swie, Javanese culture, Boekhandel, colonial period.Ã‚Â Makalah ini mengungkap cara Boekhandel Tan Khoen Swie Kediri, sebagai agen budaya Jawa, yang mengelola rumah penerbitannya di tengah-tengah pemerintah kolonial dan pemerintah Indonesia, menyebarkan budaya Jawa kepada masyarakat di Jawa dan di seluruh Indonesia. Sejarah penerbit ini menarik karena terkait dengan tiga kebijakan berbeda dari tiga jenis ideologi pemerintah. Penelitian ini yang berarti mencari, mengkritik, menafsirkan, dan mengatur sumber-sumber dalam bentuk penulisan sejarah. Penelitian ini juga menerapkan teori strukturasi Gidden untuk memperjelas posisi Tan Khoen sebagai agen penerbitan. Diskusi tentang struktur masyarakat sastra, yang terdiri dari perwakilan dari pemerintah, penulis, penerbit, dan pembaca menjadi bagian integral dari penelitian ini. Studi ini menyimpulkan bahwa pemerintah dan penerbit swasta memiliki niat untuk mendidik orang-orang meskipun Tan Khoen Swie tidak mengikat temanya pada sistem yang ada. Namun secara struktural, keberadaan Boekhandel Tan Khoen Swie dibatasi oleh penulis, penerbit lain, dan pembaca. Musim untuk menerbitkan buku-buku budaya Jawa karena buku-buku itu berisi budaya mulia, yang perlu disebarluaskan, legitimasi penulis Jawa, dan prospek pasar yang menjanjikan. Keberhasilan bisnis Tan Khoen Swie terletak pada kemampuannya membangun jejaring di antara penulis, penerbit, dan pembaca atau toko buku. Buku-buku yang diterbitkan dalam bisnisnya tersebar di seluruh Indonesia. Ia melayani baik sebagai perantara budaya dan sebagai agen budaya Jawa.Kata kunci: Tan Khoen Swie, budaya Jawa, Boekhandel, masa kolonial.Ã‚Â Ã‚Â